2018
DOI: 10.1002/bit.26810
|View full text |Cite
|
Sign up to set email alerts
|

Glycan‐masking hemagglutinin antigens from stable CHO cell clones for H5N1 avian influenza vaccine development

Abstract: Refocusing of B cell responses can be achieved by preserving the overall fold of the antigen structure but selectively mutating the undesired antigenic sites with additional N-linked glycosylation motifs for glycan-masking the vaccine antigen. We previously reported that glycan-masking recombinant H5 hemagglutin (rH5HA) antigens on residues 83, 127, and 138 (g127+g138 or g83+g127+138 rH5HA) elicited broader neutralizing antibodies and protection against heterologous clades/subclades of high pathogenic avian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Cell clones that survived following treatment with 1 mM MTX were collected and analyzed by Western blotting using anti-rH7 antibodies (GeneTex Inc.) to confirm CHO-rH7 expression. The final selected rH7-expressing clones were cultured, and the culture supernatants were harvested for rH7 purification using nickel-chelated resin affinity chromatography (Tosoh), as previously described [29][30][31]. The purified rH7 proteins were treated with endoglycosidase H (Endo H) (New England BioLabs) or N-glycosidase F (PNGase F) (New England BioLabs) for Western blotting characterization.…”
Section: Expression and Purification Of Rh7 From Stable Clones Of Chomentioning
confidence: 99%
See 1 more Smart Citation
“…Cell clones that survived following treatment with 1 mM MTX were collected and analyzed by Western blotting using anti-rH7 antibodies (GeneTex Inc.) to confirm CHO-rH7 expression. The final selected rH7-expressing clones were cultured, and the culture supernatants were harvested for rH7 purification using nickel-chelated resin affinity chromatography (Tosoh), as previously described [29][30][31]. The purified rH7 proteins were treated with endoglycosidase H (Endo H) (New England BioLabs) or N-glycosidase F (PNGase F) (New England BioLabs) for Western blotting characterization.…”
Section: Expression and Purification Of Rh7 From Stable Clones Of Chomentioning
confidence: 99%
“…Such a production method may allow semi-continuous or continuous harvesting of recombinant glycoproteins within an extended period time, thereby providing the advantage of the development of more cost-effective industrial processes [27,28]. Using CHO cell technology, we have recently obtained the high-yield producer stable cell clones for production of glycan-masking Pan-H5 vaccines [29]. Similar strategies have been also reported for production of a homogeneous HIV-1 envelope SOSIP trimer vaccine [30] and a MERS-coronavirus vaccine antigen [31].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Lin et al have shown that vaccination of hyperglycosylated HA in various formulations, such as VLPs, recombinant protein, or adenoviral vector, elicits broadly neutralizing Abs against avian influenza H5N1 viruses [ 71 , 72 ]. Another study revealed that vaccination of glycan-shielded HA antigens stably expressed by CHO cell clones increased potential neutralizing Abs against heterologous H5N1 viruses [ 73 ]. Hyperglycosylation of the HA domain does not dampen overall humoral responses, but rather changes patterns of immunodominance and elicits broadly protective Abs, as reported by Bajic et al [ 74 ].…”
Section: Ha-based Uivsmentioning
confidence: 99%
“…SP‐D, on the contrary, removes pathogens such as influenza from the lung via high mannose glycan recognition. Influenza gains glycosylation sited as it adapts to the human immune system in a yin‐yang relationship masking antigenic sites (Chen et al, 2019) but also gaining high mannose glycans which facilitate SP‐D‐dependent removal (Hsieh et al, 2018). The Siglecs are a large family of I‐type lectins with immunomodulatory function.…”
Section: Important Functional Targets Of Glycomics Analysis In the VImentioning
confidence: 99%